Chemically-mediated roostmate recognition and roost selection by Brazilian free-tailed bats (Tadarida brasiliensis). - Amy C Englert (Public Library of Science (PLoS), 2009)
Background The Brazilian free-tailed bat (Tadarida brasiliensis) is an exceptionally social and gregarious species of chiropteran known to roost in assemblages that can number in the millions. Chemical recognition of roostmates within these assemblages has not been extensively studied despite the fact that an ability to chemically recognize individuals could play an important role in forming and stabilizing complex suites of social interactions. Methodology/principal findings Individual bats were given a choice between three roosting pouches: one permeated with the scent of a group of roostmates, one permeated with the scent of non-roostmates, and a clean control. Subjects rejected non-roostmate pouches with greater frequency than roostmate pouches or blank control pouches. Also, bats chose to roost in the roostmate scented pouches more often than the non-roostmate or control pouches. Conclusions/significance We demonstrated that T. brasiliensis has the ability to chemically recognize roostmates from non-roostmates and a preference for roosting in areas occupied by roostmates. It is important to investigate these behaviors because of their potential importance in colony dynamics and roost choice.